Pengaruh Prilaku Bullying Terhadap Motivasi Belajar Siswa di Sekolah Dasar - Weni Sarbaini; Abd Aziz Tambunan (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Education is a very well-planned way to produce a generation of young people who are intelligent, brave, and talented. However, in recent years, there have been many reports of brawls and violence committed by students in schools, indicating that humanitarian values are starting to fade. The fact that bullying often occurs in schools, which reduces students' desire to learn. According to Law No. 20 of 2003 on the National Education System, schools should create a safe learning environment and support the development of students' potential. However, the practices observed in schools actually create an unsafe atmosphere, causing students to lose interest and desire to learn. The purpose of this research is to analyze the impact of bullying behavior on the learning motivation of elementary school students and to provide solutions to this problem. The method used in this research is a Systematic Literature Review (SLR) by analyzing 10 related journals published between 2015 and 2024. Data were collected through a search on Google Scholar using the keywords "the influence of bullying behavior" and "student learning motivation." The analysis includes the identification of variables, searching for relevant references, and comparing previous research results. The research results show that bullying has a significant impact on students' learning motivation. Students who are victims of bullying tend to experience anxiety, depression, and low self-esteem, which ultimately disrupt their concentration and academic performance. Several studies also found that interventions from teachers, parents, and strict school policies can reduce the negative effects of bullying. The conclusion of this research is that bullying is a serious problem that affects students' motivation and academic achievement. Therefore, a comprehensive approach involving all parties, including teachers, parents, and school policies, is necessary to create a safe and supportive learning environment. Effective prevention and intervention efforts are crucial to addressing the negative impacts of bullying in schools.